Targeted neuronal nitric oxide synthase transgene delivery into stellate neurons reverses impaired intracellular calcium transients in prehypertensive rats - Li, D; Nikiforova, N; Lu, C; Wannop, K; Mcmenamin, M; Lee, C; Buckler, K; Paterson, D (2013)
Hypertension is associated with the early onset of cardiac sympathetic hyperresponsiveness and enhanced intracellular Ca2+concentration [Ca2+]i in sympathetic neurons from both prehypertensive and hypertensive, spontaneously hypertensive rats (SHRs). Oxidative stress is a hallmark of hypertension, therefore, we tested the hypothesis that the inhibitory action of the nitric oxide-cGMP pathway on [Ca2+]i transients is impaired in cardiac sympathetic neurons from the SHR. Stellate ganglia were isolated from young prehypertensive SHRs and age-matched normotensive Wistar-Kyoto rats. [Ca2+]i was measured by ratiometric fluorescence imaging. Neurons from the prehypertensive SHR ganglia had a significantly higher depolarization evoked [Ca2+]i transient that was also associated with decreased expression of neuronal nitric oxide synthase (nNOS), β1 subunit of soluble guanylate cyclase and cGMP when compared with the Wistar-Kyoto rat ganglia. Soluble guanylate cyclase inhibition or nNOS inhibition increased [Ca2+]i in the Wistar-Kyoto rats but had no effect in SHR neurons. A nitric oxide donor decreased [Ca2+]i in both sets of neurons, although this was markedly less in the SHR. A novel noradrenergic cell specific vector (Ad.PRSx8-nNOS/Cherry) or its control vector (Ad.PRSx8-Cherry) was expressed in sympathetic neurons. In the SHR, Ad.PRSx8-nNOS/Cherry-treated neurons had a significantly reduced peak [Ca 2+]i transient that was associated with increased tissue levels of nNOS protein and cGMP concentration compared with gene transfer of Ad.PRSx8-Cherry alone. nNOS inhibition significantly increased [Ca 2+]i after Ad.PRSx8-nNOS/Cherry expression. We conclude that artificial upregulation of stellate sympathetic nNOS via targeted gene transfer can directly attenuate intracellular Ca2+and may provide a novel method for decreasing enhanced cardiac sympathetic neurotransmission. © 2012 American Heart Association, Inc.